A history of the middle ages - Steward, Tom; V. Dennett, Ashleigh; Rodrick, David; Schlessinger Media; Tremendous Entertainment Inc. (Wynnewood, PA : Schlessinger Media, 2002)
This video focusing on three distinct eras of medieval time which is the Early, High and Late Middle Ages
Teacher's guide and other resources on this topic are available online
Grades 4-8
Executive producer, Tom Steward ; written by, David Rodrick ; produced and directed by, Ashleigh V. Dennett ; editor, Robert J. Fassino...[et al.]
Keywords: Civilization, Medieval; Middle Ages -- History; Middle Ages -- Social life and customs; Social history -- Medieval, 500-1500